Adubação nitrogenada em pastagem de papuã - Salvador, Paulo Roberto (2014)
The experiment was carried out to evaluate the herbage production, sward structure, stocking rate, weight gain per area and nutritive value of forage as grazed in alexandergrass (Urochloa plantaginea (Link) Hitch) pasture fertilized with nitrogen (N). The experimental design was completely randomized following a repeated measurements arrangement. The treatments were 0; 100; 200 or 300 kg/ha of N. The experimental animals were Angus heifers with initial age and body weight of 15 month and 241.5±5 kg, respectively. The grazing method was continuous stocking with variable number of animals. The N utilization regardless of the amount increases 25% the daily herbage accumulate rate. The N fertilization increases 23% the weight gain per area. The quantity of 97.2 kg/ha of N allows greater leaf mass and increases in 20% the leaf:steam ratio. The alterations in sward structure changes the nutritive value of forage as grazed. The utilization of 112.7 kg/ha of N allows higher stocking rate (2049.8 kg/ha of BW) equivalent to 7.5 heifers per hectare.